CONDICIONANTES GEOGRÁFICOS E A FORMA URBANA DE SANTA MARIA, RS, BRASIL (Terr@ Plural, 2019)
The paper explores the urbanization process of Santa Maria, in the state of Rio Grande do Sul. The analysis was conducted according to variables and criteria related to the natural landscape, geopolitical situation, the implementation of large state and private equipment and the land parcel process. For this, historical records and municipal data were analyzed through visual observation of maps, aerial images, and photographs, with the use of geotechnologies in the elaboration of analytical maps. Finally, it analyzes the degree of interference of the natural elements of the urban landscape in the retraction or enhancement of the inductor effects of urban infrastructures and large equipment.